TIL FESTBANKET I JUNCAL: Madens sociale og kulturelle betydning hos nogle indianere i Andes - Fock, Niels (Tidsskriftet Antropologi, 1998)
Niels Fock: Banquets in Juncal: Social and Cultural Significance of Food among some Andean Indians This article is primarily an ethnographical description and analysis of food production and consumption in the Ecuadorian village of Juncal in the Canar highlands. The kind of foodstuff used, its value as nutrition and as gastronomical and dietetic regimen is analysed from cognitive and social points of view. In the near self-supplying community where money is scarce, food takes on fundamental importance in various social situations as the symbolic means of exchange. An important distinction is established between the wet daily food and the dry banquet food consumed at public feasts.